A bibliometric review on halal tourism development - Marlina, Lina; Julian, Juliana; Nasrullah, Agus Ahmad; Suhud, Usep; Inomjon, Qudratov; Sutianah, Cucu; Nuryanti, B. Lena (Edelweiss Applied Science and Technology, 2024)
This study aims to see the development of research on the topic of "Halal Tourism Development" and research plans that can be carried out based on journals published on the theme. This study uses a qualitative method with a bibliometric analysis approach. The data used are secondary data on the theme of "Halal Tourism Development" which comes from the Dimension database with the number of documents839journal articles. Then, the data is processed and analyzed using the VosViewer application with the aim of finding out the bibliometric map of the development of "Halal Tourism Development" research in the world. The results of the study found that in bibliometric author mapping the authors who published the most research on the theme of "Halal Tourism Development" were Indratno; Ratnasari, Ririn Tri; Rinuastuti, Baiq Handayani; Marlina, Lina, Mohammed Jemal, Ismanto, Kuat; Adinugraha, Hendri Hermawan; Fasa, Muhammad Iqbal; Jennah, Nurul; Heriani; and Herdiani, Aulia. Furthermore, based on bibliometric keyword mapping there are 4 clusters with the most used words being tourism development, destination, opportunity, halal tourism destination, world, attraction, strategy, community, village, Muslim tourist, factor, Muslim, and implementation. Then, the research path topics related to Halal Tourism Development are Sustainable Halal Tourism Development, Halal Tourism Supporting Infrastructure, Determinants of Halal Tourist Satisfaction, and Halal Destination Amenities Post-COVID Pandemic.